2009
DOI: 10.1002/zamm.200800222
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection between two horizontal coaxial cylinders

Abstract: The objective of our paper is to start the theoretical investigation of the most commonly used mathematical model for natural convection in a horizontal annulus. First, one shows existence of solutions for the unsteady problem. Then, for any Prandtl number and inverse relative gap width, existence, and stability of a steady solution is proved, provided that the Rayleigh number is sufficiently small. The same is also proved for any Rayleigh number provided the inverse relative gap width is sufficiently small. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…In 2004, Passerini et al [12] performed a theoretical investigation about the free convection in horizontal concentric cylinders. They showed that, for su ciently small Rayleigh numbers, a steady stable solution can be obtained.…”
Section: Literature Surveymentioning
confidence: 99%
“…In 2004, Passerini et al [12] performed a theoretical investigation about the free convection in horizontal concentric cylinders. They showed that, for su ciently small Rayleigh numbers, a steady stable solution can be obtained.…”
Section: Literature Surveymentioning
confidence: 99%
“…This means that even the most simplified model problem for natural convection in horizontal annuli has not been solved analytically. Thus, in the domains we are considering, the analytical study of the dynamical system is still in an initial phase (see [19]). …”
Section: Mathematical Modelmentioning
confidence: 99%
“…In [19] it is shown that for sufficiently small Ra a solution can always be found for system (3)(4)(5). However, a simpler system would be easier to handle.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…In the geometry given here, some theoretical properties of Boussinesq's system can be found in Ferrario et al (2010) and Passerini et al (2009). On the other hand, a comprehensive review of the available experimental data and numerical results for heat transfer in a horizontal circular annulus has been presented by Teerstra and Yovanovich (1998).…”
mentioning
confidence: 92%
“…In the light of Kuehn and Goldstein (1976), Passerini et al (2009) and Powe et al (1969) what should be expected for small Ra and any A is a steady unicellular flow (see, e.g. Fig.…”
mentioning
confidence: 95%